Takio. [01] - Bendis, Brian Michael (Marvel Worldwide, Inc., 2011)
"Two sisters in a multi-racial, adoptive family are driving each other insane! Their overprotective mother makes them walk to school together, eat lunch together and play together. They can't get away from each other! But when a one-of-a-kind, once-in-a-lifetime accident gives them real-life superpowers, these two sisters become the first actual superheroes in the entire world. And it is awesome! Now the sisters have to learn to get along so they can save the world and get home by six-- or they are so grounded" -- p. [4] of cover.